102 Patient Safety in Neurosurgical Practice: Physician Factors that Contribute to Patient Injury. (August 2016) - Taylor, Christopher L.; Ranum, Darrell
Abstract : INTRODUCTION: We identified the primary factors that contributed to patient injury in neurosurgical practice. METHODS: Medical malpractice claims (n = 355) from The Doctors Company that were closed over 7 years were reviewed by neurosurgical medical experts. The reviewers provided objective analyses of the cases including identification of patient injuries and the primary factor that contributed to the patient injury. RESULTS: For all claims, continued pain, nerve damage, and need for additional surgery were the most common injuries. Assessment (evaluation and diagnosis), selection and management of therapy, and communication between the physician and patient/family were the primary factors that contributed to patient injury in 145 cases (40.8%). Surgical complication (a known risk of the procedure) was the primary factor in 99 cases (27.9%), while technical performance of surgery was the primary factor in only 39 cases (11.0%). CONCLUSION: The primary factor contributing to patient injury was evenly divided between the perioperative period and outside the perioperative period. Within the perioperative period, a known risk of the procedure was the primary factor approximately 2.5 times more often than technical performance. Technical performance of surgery caused patient injury in a minority of cases. Improving patient safety in neurosurgical practice requires careful attention to differential diagnosis, consideration of all relevant clinical data, active pursuit of good physician-patient relationships, careful attention to the perioperative period, and adequate monitoring of patients receiving nonsurgical treatment. The consent process should be improved to better help patients understand the possible outcomes of surgery.